Set-level strategic and psychological momentum in best-of-three-set professional tennis matches - Depken, C. A.; Gandar, J. M.; Shapiro, D. A. (Journal of Sports Economics, 2022)
We provide a theoretical and empirical analysis of strategic momentum and psychological momentum in best-of-three contests between players with unequal skills. As a theoretical benchmark, we develop a fully rational model of best-of-three contests and define psychological momentum as systematic deviation from the theoretical equilibrium. An empirical analysis of 66,262 professional tennis matches from 2002 to 2020 shows that our theoretical model closely matches first set outcomes, which is when set-level psychological momentum is absent. Overall, the empirical results show that both strategic momentum and psychological momentum contribute to the outcomes of best-of-three tennis contests.